Genetic diversity of BoLA-DRB3 in Latin American Creole cattle: an update of the state of the art - Marcuzzi, Olivia (2025)
Genetic diversity of the bovine leukocyte antigen BoLA-DRB3 gene has been reported in cattle breeds due to its central role in immune response. However, the gene has been characterized in only a few Latin American native cattle breeds. In this study, we aimed to investigate the genetic diversity of this gene in other native bovine breeds from Argentina, Bolivia, Cuba, and Paraguay, thereby contributing to the global knowledge regarding BoLA-DRB3 diversity. The gene was genotyped using PCR-sequence-based typing; 60 reported alleles and one novel variant were identified. The observed and expected heterozygosity values were higher than 0.81, and only two populations showed deviation from the Hardy-Weinberg equilibrium. The Slatkin neutrality test indicated even allele distribution in one population. Nucleotide diversity and the number of pairwise differences ranged from 0.073 to 0.081 and 17.88 to 20.19, respectively. The mean number of non-synonymous and synonymous nucleotide substitutions was estimated for the entire sequence and the antigen-binding site (ABS), with higher values observed in the latter. Amino acid motifs varied in their frequencies, and the diversifying selection index (ω) at each amino acid was high in more than 25 sites, with the most prominent peaks located in the ABS. A distribution of native cattle according to their historical and geographical origin and degree of Zebu gene introgression demonstrated that the Latin American native populations exhibit high variability in the BoLA-DRB3 gene, including private alleles, and a distinct genetic profile, making them a valuable genetic resource and emphasizing the importance of their conservation.